Legal Study on Health Service Facilities for Company Employees During the COVID-19 Pandemic - Andhika Budi Sentoso (Medistra Medical Journal (MMJ), 2025)
The COVID-19 pandemic transformed patterns of employment, occupational safety, and access to health services for company employees. The high rate of SARS-CoV-2 transmission since early 2020 led to public health control measures such as social distancing, mandatory masking, and remote working arrangements (Work From Home/WFH). This situation raises a legal question: to what extent are employers obligated to ensure employee health and safety as part of the right to health, particularly when work must continue under a public health emergency. This study is a normative (doctrinal) legal research with a descriptive qualitative approach. Primary legal materials include Law No. 17 of 2023 on Health, national regulations on occupational safety and health, Ministry of Health guidance for COVID-19 prevention in the workplace, and World Health Organization recommendations on worker protection during infectious disease outbreaks. Secondary legal materials include health law scholarship, occupational health literature, and recent international publications addressing worker protection during the COVID-19 pandemic. Data were analyzed by interpreting applicable legal norms and assessing their practical relevance to the fulfillment of employees’ right to health in corporate settings. he findings indicate that the obligation to provide health service facilities for employees extends beyond curative access and includes preventive and promotive measures such as periodic health screening, staggered/shift-based work arrangements, reduced physical contact, virtual communication systems, provision of basic protective equipment, and guaranteed referral pathways to health services. These obligations are consistent with the principles of the right to health, occupational safety and health (OSH), and worker protection under Indonesian law. However, implementation faced barriers including fear and stigma, misinformation, and unequal company resources.